The role of soluble urokinase plasminogen activator receptor (suPAR) in patients with cancer: a review of the current literature - Themistoklis Paraskevas; Francesk Mulita; Christos Michailides; Georgios-Ioannis Verras; Elias Liolis; Eleousa Oikonomou; Ioannis Perdikaris; Panagiotis Perdikaris; Konstantinos Bouchagier; Ioannis Panagiotopoulos; Dimitrios-Ioannis Kasartzian; Dimitrios Filis; et al. (Medicinski glasnik, 2022)
Aim: Several biomarkers are currently used as diagnostic and prognostic tools in patients with cancer. Soluble urokinase plasminogen activator receptor (suPAR) is elevated in acute and chronic inflammatory procedures and several observational studies during the last 20 years have investigated its role in oncology. The purpose of this article was to review the current literature regarding suPAR’s role in clinical practice. Methods: A systematic literature search of PubMed, Scopus, OpenGrey and Cochrane Library databases through September 2021 was conducted using the following search terms: “supar” or “soluble urokinase plasminogen receptor” and “cancer” or “malignancy”. Original articles reporting on suPAR’s role in the diagnosis, prognosis and prediction of therapeutic outcomes in patients with confirmed or suspected cancer were included. Results: Among 45 found articles, the most were observational cohort studies. The included studies were further categorized by cancer site. SuPAR level was higher in patients with cancer compared to healthy controls, but its diagnostic and prognostic accuracy differs depending on the site of cancer. Conclusion: SuPAR has promising aspects in the field of oncology and public health and future research should further investigate its use in clinical practice. As it is elevated in different types of cancer, it could potentially serve as an adjunctive tool for the mass screening of patients with non-specific signs of cancer, but larger cohort studies that support these findings must be conducted.
Keywords: biomarker; diagnosis; neoplasms; prognosis